A day late and a dollar short: Intertemporal revenue cap regulation considering stranded assets - Maria Nussberger; Hendrik Diers; Philipp Artur Kienscherf (Institute of Energy Economics at the University of Cologne (EWI), 2025)
The European Union's goal of carbon neutrality by 2050 requires a major reduction in natural gas use for residential heating. However, gas grid equipment, amortized over 45 years in most countries, risks becoming stranded assets. The literature suggests that regulatory shocks could justify enhanced cost recovery during the remaining grid use period to reduce social costs of asset stranding. Under revenue cap regulation, increased cost recovery and higher tariffs may prompt households to switch to alternative technologies. These premature defections risk undermining cost recovery and place additional financial burdens on remaining households. Regulators face a trade-off between efficient defections and cost recovery. This paper introduces an intertemporal equilibrium model to explore network tariffs and household responses under different revenue caps and analyze their welfare implications. We demonstrate that degressive front-loading is an optimal strategy, balancing cost recovery with household exits, reducing stranded assets, and minimizing social costs. Furthermore, we find that, under the predominant revenue cap schemes, total cost recovery is often not achieved. We also examine distributional implications, showing how tariffs burden heterogeneous households. This research offers insights for policymakers and regulators into mitigating stranded costs while managing household defection impacts in countries with revenue cap regulation and young gas grids.
Keywords: D15; D42; D63; L12; L38; L42; L51; L95; 330; Gas; regulation; revenue caps; network tariffs; household response